Magnetic frustration of graphite oxide - Lee, Dongwook (2017)
Delocalized π electrons in aromatic ring structures generally induce diamagnetism. In graphite oxide, however, π electrons develop ferromagnetism due to the unique structure of the material. The π electrons are only mobile in the graphitic regions of graphite oxide, which are dispersed and surrounded by sp3-hybridized carbon atoms. The spin-glass behavior of graphite oxide is corroborated by the frequency dependence of its AC susceptibility. The magnetic susceptibility data exhibit a negative Curie temperature, field irreversibility, and slow relaxation. The overall results indicate that magnetic moments in graphite oxide slowly interact and develop magnetic frustration.